PROTECTIVE ROLE OF 2-BORNEOL IN THE EMERGENCE OF Allium cepa SEEDS EXPOSED TO NaCl - Larisse Bernardino dos Santos; Jailson Renato de Lima Silva; Carlos Vinicius Barros Oliveira; Adrielle Rodrigues Costa; Maria Keliane Alves de Souza; Thalyta Julyanne Silva de Oliveira; Daniel Honorato Neves; José Wellington Macêdo Viana; Antonio Ivanildo Pinho; Pedro Silvino Pereira; et al. (South American Journal of Basic Education, Technical and Technological, 2022)
It has been proposed that borneol acts as a compound responsible for inducing tolerance to salt stress in the Allium cepa model organism. This study investigated the effect of borneol variation (100, 300 and 500 µg/mL) on the phytotoxic potential in seed emergence, growth of seedlings, roots and leaves in A. cepa under field conditions, normal and induced by NaCl (150 mM). Changes in and lipid peroxidation (LPO) levels was evaluated as markers of oxidative stress, and the antioxidant activity of borneol was evaluated by DPPH test. The exposure of A. cepa to 150 mM of NaCl significantly decreased the emergence capacity of the seeds. Nevertheless, borneol at concentrations of 100 and 300 µg/mL significantly reduced the salt stress and improved the emergence rate and the number of roots. Borneol significantly reduced lipid peroxidation (LPO) caused by NaCl, but, did not have any effect on the total iron content. Borneol exhibited DPPH radical scavenging activity similar to that of ascorbic acid used as standard antioxidant. The nutrients with the highest accumulation in the soil were P> S> Ca> N> K> Mg. Moreover, the pH was ideal for the cultivation of the species. The results of this study suggest that borneol can be used as a potential tolerance regulator to improve resistance to salt stress in Allium cepa.